2021
DOI: 10.1016/j.phrs.2021.105581
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the heart-brain axis response in COVID-19 patients: A suggestive perspective for therapeutic development

Abstract: In-depth characterization of heart-brain communication in critically ill patients with severe acute respiratory failure is attracting significant interest in the COronaVIrus Disease 19 (COVID-19) pandemic era during intensive care unit (ICU) stay and after ICU or hospital discharge. Emerging research has provided new insights into pathogenic role of the deregulation of the heart-brain axis (HBA), a bidirectional flow of information, in leading to severe multiorgan disease syndrome (MODS) in patients with confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 180 publications
0
42
0
4
Order By: Relevance
“…SARS-CoV-2 triggers a dysfunction in endothelial cells, causing apoptosis ( Varga et al, 2020 ). This conception is supported by the fact that microvascular endothelial cells express ACE2 and, therefore, are susceptible to SARS-CoV-2 entry ( Lionetti et al, 2021 ). The vascular and neuronal circulation of SARS-CoV-2 is thought to induce heart-brain axis (HBA) dysfunction ( Lionetti et al, 2021 ).…”
Section: Mechanisms Of Sex Differences In Covid-19 Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 triggers a dysfunction in endothelial cells, causing apoptosis ( Varga et al, 2020 ). This conception is supported by the fact that microvascular endothelial cells express ACE2 and, therefore, are susceptible to SARS-CoV-2 entry ( Lionetti et al, 2021 ). The vascular and neuronal circulation of SARS-CoV-2 is thought to induce heart-brain axis (HBA) dysfunction ( Lionetti et al, 2021 ).…”
Section: Mechanisms Of Sex Differences In Covid-19 Pathogenesismentioning
confidence: 99%
“…ACE2 is also expressed in neurons ( Yashavantha Rao and Jayabaskaran, 2020 ). SARS-CoV-2 could enter the central nervous system (CNS) and cause neurological diseases by impairing the crosstalk between neuronal and vascular components of the CNS ( Desforges et al, 2014 ; Lionetti et al, 2021 ). SARS-CoV-2 triggers a dysfunction in endothelial cells, causing apoptosis ( Varga et al, 2020 ).…”
Section: Mechanisms Of Sex Differences In Covid-19 Pathogenesismentioning
confidence: 99%
“…ROS are involved in several biological processes such as cellular growth, immune response, embryogenesis, spermatozoa capacitation, and transcription factor activation [ 44 , 65 ]. Furthermore, ROS regulate vascular functions (e.g., vasodilatation, vasoconstriction, angiogenesis, migration, and apoptosis) [ 41 , 44 , 45 , 46 ]. Thus, there is a finely regulated balance between ROS production and ROS degradation [ 46 ].…”
Section: Ros Production and Elimination In Endothelial Cellsmentioning
confidence: 99%
“…TRPM2 was also found to mediate H 2 O 2 -induced cell death in brain microvascular endothelium [ 228 ]. In addition to providing the building blocks for the BBB [ 293 ], brain microvascular endothelial cells are emerging as crucial regulators of neuronal activity and cerebral blood flow under both physiological and pathological conditions [ 24 , 25 , 41 ]. Iadecola’s group first showed that amyloid β 1-40 (Aβ 1-40 ), whose extracellular accumulation on brain microvessels is now regarded as the primary trigger of the pathogenic pathways leading to neuronal damage and dementia [ 294 ], may induce endothelial dysfunction by promoting TRPM2-mediated cytosolic Ca 2+ overload [ 38 ].…”
Section: Therapeutic Applications and Pathological Implications Of Ros-induced Endothelial Ca 2+ Signalsmentioning
confidence: 99%
See 1 more Smart Citation